Hydrocarbon Generation and Accumulation in the South Junggar Basin, Northwest China: Insights From Basin Modeling - Liu, Yuming; Lu, Xuesong; Zhao, Mengjun; Zhuo, Qingong; Gui, Lili (Frontiers in Earth Science, 2022)
The South Junggar foreland basin is characterized by fold-and-thrust deformation caused by the Cenozoic India–Tibet collision and uplift of the Tianshan Mountains. The tectonic deformation and hydrocarbon accumulation in this region show east–west, north–south, and vertical zoning. Four sets of source rocks are present in the basin, which are middle Permian, Middle–Early Jurassic, Early Cretaceous, and Paleogene in age. The various source rocks are vertically stacked, and thus form a composite petroleum system. Due to differences in source rocks, burial history, hydrocarbon generation, and structural traps formation, the accumulation and distribution of oil and gas is spatially variable. In this paper, we present a detailed analysis on hydrocarbon generation and accumulation in SJFB by basin modelling both in 1D and 2D, including the different burial and hydrocarbon generation histories in different regions, the effective distribution and contribution of the four sets of source rock to oil and gas reservoirs. Four types of burial and thermal evolution history has been classified, which corresponds to the different hydrocarbon phase and maturity. The heterogeneous distribution of oil and gas reflects the variable source rock distribution and maturity evolution, and relative timing of hydrocarbon generation and formation of structural traps.The timing of structural trap formation in the second and third row of anticlines was later than the main phase of hydrocarbon generation, which may explain the poor exploration outcomes in the SJFB. The result indicates that Jurassic and Cretaceous formations in the middle segment of fold-and-thrust belt in SJFB are the most favorable combination for hydrocarbon accumulations, and have high potential for gas exploration.